A Study on the Speaking Skill at Second Year Students in Madrasah Aliyah Swasta Kepenuhan in Stating Expressions - Afrifa, Siti; Rahayu, Pipit; Kasyulita, Evi (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
This research was descriptive research. The total of number population were 42 students which devide into 3 class.the researcher random took as the sample which total 42 students. To select the sample the resercher used random sampling. The data of this research was score in stating expressions.From 42 students 25 students (59,52%) got average score. And 17 students (40,47) got fair. Based on the finding of the research,it can be suggested that (1) the English teacher should be spirit and never give up in teaching students. (2) the students should more seriously in studied.